An Excursion as a Great Medium of Writing Process to Teach Writing - Rusdiana Junaid; Rustan Santaria (Institut Agama Islam Negeri Palopo, 2022)
Generally, most English language learners believed that writing is the most difficult language skill to perform. In addition, some English teachers/lecturers experience difficulties to encourage and motivate their students to write. There are a number of reasons why sometimes many language learners find it difficult to perform writing skills. One of the reasons is that they are sometimes asked to write about the topics they have little knowledge of. Another reason is if they are not interested in the topics they are asked to write about. This paper aims at describing one way in which English teachers can help their students get as much out of activity as possible despite their writing experiences, that is through an excursion. An excursion is a great way of encouraging and motivating the students to practice their writing skills. Data were obtained through observation of the field trip and written tasks performed by 32 of the fourth semester students of English Education Study Program, in academic year 2016/2017 at Cokroaminoto University, Palopo. Data obtained were analyzed qualitatively. The result of the research reveals that an excursion is an appropriate way for tackling the written tasks which are sometimes daunting for English language learners to perform. Such activity facilitates the students to write enthusiastically since the students know the subject matter they are writing about. In addition, through several activities in an excursion, the students can improve their vocabulary command, increase their grammatical knowledge, develop their English language skills in general and build up their self-confidence, particularly in performing writing tasks.Â Â